Tantangan Guru Pendidikan Kewarganegaraan di Masa Adaptasi Kebiasaan Baru - T. Heru Nurgiansah; Sukmawati (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2020)
The New Habit Adaptation Period (AKB) began after the Covid-19 virus outbreak in Indonesia. The implementation of health protocols applies in all activities including education such as online learning enforcement, keeping distance, avoiding crowds, and wearing Personal Protective Equipment. This is a challenge for citizenship education teachers in the Special Region of Yogyakarta. This research aims to analyze the challenges facing Citizenship Education teachers and their solutions. Research methods use qualitative with data collection techniques in the form of observation, interview, documentation, and literacy. The results of this study show that the most difficult challenge for Citizenship Education teachers in this new habit adaptation period is online learning, so training is needed for teachers in technology to support learning.